PENGARUH CITRA MEREK, KUALITAS PRODUK, DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN TOYOTA AGYA: Penelitian Pada Konsumen Mobil LCGC Di Kota Depok - Aryo Kuncoro Mukti Darmawan (2021)
This study aims to measure and determine how much influence brand image, product quality, and price have on purchasing decisions for Toyota Agya in Depok City. The target population is LCGC car consumers in Depok City with a sample of 70 respondents. Collecting data using non-probability sampling method and distributed using an online questionnaire. The data analysis technique used is Partial Least Square (PLS). The results of this study indicate that (1) Brand Image has no influence on the Toyota Agya Purchase Decision in Depok City, (2) Product Quality has a significant influence on the Toyota Agya Purchase Decision in Depok City, (3) Price has a significant influence on the Purchase Decision. Toyota Agya in Depok City, (3) Price has a significant influence on the Purchase Decision of Toyota Agya in Depok City.